Accountability for sexual and reproductive health and rights in development practice: building synergies. Issue 1 (1st January 2020) - Barragués Fernández, Alfonso
Abstract: The 2030 Agenda for Sustainable Development is the culmination of 25 years of global efforts to embed human rights in the development discourse. Epitomising the principle of Leaving No-one Behind, the 2030 Agenda contains concrete references to the realisation of human rights as the ultimate purpose of sustainable development as well as to governments' accountability towards citizens. Despite this compelling narrative, the information produced by States in reviewing progress on Sustainable Development Goals (SDGs) reveals a gap between rhetoric and practice. Voluntary National Review (VNR) reports have emerged as a central tool to inform and guide the national and global reviews of SDGs progress. The UN system recommends that States build upon information from existing platforms, the Universal Periodic Review (UPR) and UN Treaty Bodies, in order to reduce reporting burdens. However, an analysis of information on Sexual and Reproductive Health and Rights (SRHR) in VNR reports from 12 countries shows that States are missing the opportunity to build on the wealth of information they themselves have produced in their engagement with human rights mechanisms. Although many first generation VNRs did not come across as very substantive, their emphasis on participation and multi-stakeholder dialogue has created important, and sometimes unprecedented, national political traction for civil society. This engagement can be built upon to inject a human rights perspective towards the achievement of more equitable development outcomes.